Conflictos ambientales y extractivistas en américa latina - Ramón Cimadevilla, Gustavo; Arancibia Martínez, Leticia; Pesquero Bordón, Jimena; Lagunas Cerda, Samuel; Torres Salinas, Robinson; Bárbara Jerez Henríquez, Bárbara; Trujillo Avila, Stephany Argelia; Montano Peña, Montserrat; Iño Daza, Weimar Giovanni; Casas Matiz, Elvia Isabel; Abello Avila, Nataly (Universidad Santiago de Cali, 2025)
Published